Approaches to Project Management in the Process of Digital Transformation in the Company - Tatiana Corejova; Peter Bielik; Tatiana Genzorova (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
As digital technologies evolve, proven business practices are disrupted and companies need to respond to the benefits of digitization. Most often it is said to have a great impact on the traditional business model and its change. Based on the analysis of the current situation and experience in the practice of changes caused by digitization, the aim of the paper will be to compare and point out the possibilities of different approaches to project management in the process of digital transformation in the company. Especially waterfall and agile approaches will be tested. The aim of the proposal is to find a link between the waterfall and agile model of project management in systematic response in the digital transformation process. The classic framework is maintained externally, other techniques that ensure continuous creation in a shorter time frame will be used to find a solution to the problem. If a company wants to change its business model, first of all, it must start inside, without the momentum and potential that it has in its employees, it is not able to easily and correctly in the given conditions to handle. According to the World Economic Forum (2016), waterfall project management no longer meets the requirements of digitization and the company should focus on management that is agile.
Keywords: O31; O32; 330; digital transformation; project management; waterfall approach; agile approach; design thinking